Modeling cross-shore profile evolution in response to climate change: A case study for the Southwestern Black Sea Coast - Guner, H. Anil Ari; Basaran, Busra (ELSEVIER, 2024)
Changes in wave climate and sea level as a result of global climate change cause significant effects on coastal morphology. Especially increasing wave heights, more frequent storms, and sea level rise (SLR) significantly alter the morphology of cross-shore profiles and diminish the security of coastal areas. In this study, profile surveys were carried out in two distinct regions along the Western Coast of the Black Sea, and the profile evolutions were analyzed using the XBeach numerical model. The XBeach model was executed using both its default parameters and the parameters derived from on-site measurements. This study was also conducted under the influence of hydrodynamic conditions (wave parameters) that vary according to the RCP4.5 and RCP8.5 climate scenarios, along with the effects of sea level rise (SLR), to analyze the potential impacts of climate change on profile evolution. The results indicated a linear relationship between the upper beach erosion and sea-level rise (SLR). The increased water level in front of the upper beach leads to greater erosion volume. The model results for the scenarios demonstrated moderate sensitivity to variations in offshore wave height, peak wave period, and storm duration, but were predominantly sensitive to accelerated sea level rise (SLR).
Keywords: Morphodynamic modeling; Cross-shore sediment transport; XBeach; Wave climate change; Sea level rise (SLR); Southwestern Black Sea; Karasu coast; DUNE EROSION; EMILIA-ROMAGNA; STORM CLUSTERS; CHANGE IMPACTS; WAVE CLIMATE; HIGH-ENERGY; BEACH; SANDY; PREDICTIONS; Environmental Sciences & Ecology; Marine & Freshwater Biology